The speed of risk : lessons learned on the audit trail - Chambers, Richard F.; Institute of Internal Auditors. Research Foundation; Institute of Internal Auditors (Lake Mary, Fla : The Internal Audit Foundation, 2019)
In this 2nd edition of Lessons Learned on the Audit Trail, author Richard Chambers shares fresh perspectives on the lessons in the first edition and imparts new lessons learned during the last few years. He has invested more than four decades serving the profession. His belief and motivation in writing this new edition is that if he can help just one internal auditor to be better prepared for the challenges and opportunities that lie ahead, then the effort will have been worth it. In the years since the first edition was published, Richard Chambers has shared numerous new lessons across various content media presentations, social media, and more than 200 blogs and articles. The speed of risk has been a recurring theme in the messages he has delivered to the profession since 2014, and it is a theme that is prominent in this updated edition. He offers fresh perspectives on key developments from recent years that have critical implications for the profession. His hope is that readers will find his journey worthwhile and learn how to harness their own personal passion for the internal audit profession. The author addresses topics of concern to the profession today, including: The rising expectations of internal audit's stakeholders The imperative to audit at the speed of risk How internal audit must leverage innovation in the face of disruption Internal audit s role in auditing culture, artificial intelligence, and new technologies The idea that internal auditors can audit anything but not everything The skills future trailblazers will need in internal audit.
Sponsored by the Institute of Internal Auditors, Chicago Chapter.
Keywords: Auditing, Internal; Auditors; Risk management